1984
DOI: 10.1021/bi00303a002
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of myosin synthesis by thyroid hormone: relative change in the .alpha.- and .beta.-myosin heavy chain mRNA levels in rabbit heart

Abstract: The expression of mRNAs for two cardiac myosins has been examined in the ventricles of hypo- and hyperthyroid rabbits by means of cloned cDNA sequences corresponding to the mRNAs of the alpha- and beta-myosin heavy chains (HCs). The temporal change in the relative levels of the alpha- and beta-HC mRNAs after 3,5,3'-triiodothyronine (T3) treatment of hypothyroid rabbits was determined by nuclease S1 mapping. In the hypothyroid state, only HC beta-mRNA was expressed in the ventricles. The HC alpha-mRNA was first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
0

Year Published

1987
1987
2007
2007

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(49 citation statements)
references
References 15 publications
3
46
0
Order By: Relevance
“…We and others have previously shown that the cardiac MHC isozyme transition during normal development and thyroid hormone manipulation is regulated by changes in the levels of the respective mRNAs (20,33), which in turn appear to be transcriptionally regulated. Furthermore, the preliminary results of nuclear run-off experiments suggest that thyroid hormone regulates the a-and ,B-MHC genes at the level oftranscription, and not by changes in mRNA half-life (34).…”
Section: Resultsmentioning
confidence: 97%
“…We and others have previously shown that the cardiac MHC isozyme transition during normal development and thyroid hormone manipulation is regulated by changes in the levels of the respective mRNAs (20,33), which in turn appear to be transcriptionally regulated. Furthermore, the preliminary results of nuclear run-off experiments suggest that thyroid hormone regulates the a-and ,B-MHC genes at the level oftranscription, and not by changes in mRNA half-life (34).…”
Section: Resultsmentioning
confidence: 97%
“…Proteolytic fragment S1, corresponding to myosin head domain and two other proteolytic fragments, S2 and LMM (light meromyosins) corresponding to alpha-helical rod domain are shown. (C) Schematic representation of the developmental regulation of rat and rabbit heart myosin isoforms during fetal, adult and old age of the animal [15,16,154]. Increased activity of PARP1 in physiologic and pathologic hypertrophy.…”
Section: Future Directionsmentioning
confidence: 99%
“…Overall, protein synthesis is enhanced (Michels, Cason & Sokoloff, 1963), with an increase in oxidative metabolism and glycolytic capacity (Seymour, Eldar & Radda, 1990). The improvement in cardiac performance is largely due to shifts in myosin isoform distribution, so that the V1 form predominates (Dillmann, 1984;Everett et al 1984). The faster ATPase action of this isoform underlies the enhanced speed of contraction.…”
Section: Introductionmentioning
confidence: 99%